Avaliação da espectrometria no infravermelho próximo na determinação de C e N de solos da região Sul do Espírito Santo - Vieira, Camila Fernandes (2019)
The present study aimed to investigate the predictive capacity of total organic carbon and nitrogen contents by means of near infrared reflectance spectroscopy (NIR) and its potential for use in routine soil analysis. This method presents greater agility